2015
DOI: 10.1371/journal.pone.0136023
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 and PD-L1 Expression in NSCLC Indicate a Favorable Prognosis in Defined Subgroups

Abstract: BackgroundImmunotherapy can become a crucial therapeutic option to improve prognosis for lung cancer patients. First clinical trials with therapies targeting the programmed cell death receptor PD-1 and its ligand PD-L1 have shown promising results in several solid tumors. However, in lung cancer the diagnostic, prognostic and predictive value of these immunologic factors remains unclear.MethodThe impact of both factors was evaluated in a study collective of 321 clinically well-annotated patients with non-small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
149
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(184 citation statements)
references
References 33 publications
16
149
2
1
Order By: Relevance
“…It is in line with a recent report, showing that PD-1 þ T infiltrating lymphocytes and PD-L1 þ tumor cells were both favorable prognostic factors in ovarian cancer (41). The inverse function of the immune checkpoint molecules in controlling the T-cell activation in other types of cancers was also suggested by several other independent studies (42)(43)(44). As a matter of fact, some of the B7-CD28 members, such as CTLA-4, have been reported to brake T regulatory cell proliferation driven by CD28 (45) or to inhibit CD28 costimulation by depleting the ligands (46).…”
Section: Discussionsupporting
confidence: 90%
“…It is in line with a recent report, showing that PD-1 þ T infiltrating lymphocytes and PD-L1 þ tumor cells were both favorable prognostic factors in ovarian cancer (41). The inverse function of the immune checkpoint molecules in controlling the T-cell activation in other types of cancers was also suggested by several other independent studies (42)(43)(44). As a matter of fact, some of the B7-CD28 members, such as CTLA-4, have been reported to brake T regulatory cell proliferation driven by CD28 (45) or to inhibit CD28 costimulation by depleting the ligands (46).…”
Section: Discussionsupporting
confidence: 90%
“…Most studies have emphasized an association between high PD-L1 expression and poor survival based on the ability of PD-L1 to negatively regulate antitumor T-cell responses. In contrast, high PD-L1 expression has been linked to better prognosis in some malignancies (17,35,37). In these reports, a significant association between high PD-L1 expression and increased TILs was identified (17,34,35,37).…”
Section: Discussionmentioning
confidence: 93%
“…The prognostic value of PD-L1 expression has been investigated for various malignancies, including malignant melanoma, nonsmall cell lung cancer, and renal cell carcinoma (34)(35)(36). Most studies have emphasized an association between high PD-L1 expression and poor survival based on the ability of PD-L1 to negatively regulate antitumor T-cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies suggesting a negative prognostic role (17,(21)(22)(23), while others did not find any prognostic value (24,25). However, other studies reported improved patient outcomes (20,26). This discrepancy may be due to different PD-L1 immunohistochemistry assays, using variable detection antibodies and different cutoff.…”
Section: Resultsmentioning
confidence: 99%